EL DESARROLLO DE LA COMPRENSION LECTORAL Y LA APLICACIÓN DE FICHAS DE LECTURA EN EL APRENDIZAJE DE LA ASIGNATURA DE LENGUA Y LITERATURA DE LOS ESTUDIANTES DEL COLEGIO FISCAL MIXTO ''ELOY ALFARO'' DEL CANTON QUEVEDO. - ARREAGA MUÑOZ BETTY ARACELY (2013)
THE DEVELOPMENT OF READING COMPREHENSION AND THE APPLICATION OF READING SHEETS IN THE LEARNING OF THE SUBJECT OF LANGUAGE AND LITERATURE OF THE STUDENTS OF THE MIXED TAX SCHOOL ''ELOY ALFARO'' OF CANTON QUEVEDO.